Some correlates of risky user behavior and ICT security awareness of secondary school students - Borić Letica, Ivana (Array, 2020)
The aim of the research was to examine some correlates of security awareness and risky behavior while using information technology. The sample consisted of 206 participants; i.e., 150 female and 56 male students from three secondary schools. The Users’ Information Security Awareness Questionnaire, the Consciousness Subscale and the Self-Control Questionnaire were used. Results showed that there are statistically significant (low to moderate) correlations between some personality traits (self-control and consciousness) and time spent on the Internet, borrowing access data, different risky behaviors, computer maintenance and proper data storage. Adolescents show low levels of security awareness. Parents talk more about privacy and security risks with girls than with boys. Girls show more security awareness than boys but behave equally risky. Those with whom parents talk more about security risks show less risky behavior and more security awareness.